PATH FORMING DIGITAL COMPETENCE OF TEACHERS IN DISCUSSION DISTANCE TEACHING - Issabayeva Д.Н.; Nazkenova Б.Б.; Mekebayev Н.О. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article considers changes in the education system during the covid-19 coronavirus pandemic. Introduced the term "digital competence of the teacher" and conducted a comparative analysis of the relationship of teachers and students to distance learning through the sociological survey. The main disadvantage of distance learning is that the teacher considers that there is no direct contact with the student, and students feel uncomfortable, because they can not teach directly to the teacher. The problem of distance learning and the development of a course program to enhance the digital competence of teachers have been identified. The course covers the basics of pedagogical design, sections of educational results, platforms for joint work, tools for creating video lectures, platforms for monitoring and collection of information, digital surveillance and laboratory analysis, online analysis. As a result of the training, 680 teachers from Kazakhstan universities and teachers of secondary schools developed their own courses and tested them at the end of the first semester. The authors conducted a two-step procedure for the analysis of data using the methods of deductive and inductive analysis. Many of the problems identified by the course indicators have been significantly reduced.